The fish embryo toxicity test as an animal alternative method in hazard and risk assessment and scientific research - Embry, Michelle R.; Braunbeck, Thomas (Aquatic toxicology, 2010)
Animal alternatives research has historically focused on human safety assessments and has only recently been extended to environmental testing. This is particularly for those assays that involve the use of fish. A number of alternatives are being pursued by the scientific community including the fish embryo toxicity (FET) test, a proposed replacement alternative to the acute fish test. Discussion of the FET methodology and its application in environmental assessments on a global level was needed. With this emerging issue in mind, the ILSI Health and Environmental Sciences Institute (HESI) and the European Centre for Ecotoxicology and Toxicology of Chemicals (ECETOC) held an International Workshop on the Application of the Fish Embryo Test as an Animal Alternative Method in Hazard and Risk Assessment and Scientific Research in March, 2008. The workshop included approximately 40 scientists and regulators representing government, industry, academia, and non-governmental organizations from North America, Europe, and Asia. The goal was to review the state of the science regarding the investigation of fish embryonic tests, pain and distress in fish, emerging approaches utilizing fish embryos, and the use of fish embryo toxicity test data in various types of environmental assessments (e.g., hazard, risk, effluent, and classification and labeling of chemicals). Some specific key outcomes included agreement that risk assessors need fish data for decision-making, that extending the FET to include eluethereombryos was desirable, that relevant endpoints are being used, and that additional endpoints could facilitate additional uses beyond acute toxicity testing. The FET was, however, not yet considered validated sensu OECD. An important action step will be to provide guidance on how all fish tests can be used to assess chemical hazard and to harmonize the diverse terminology used in test guidelines adopted over the past decades. Use of the FET in context of effluent assessments was considered and it is not known if fish embryos are sufficiently sensitive for consideration as a surrogate to the sub-chronic 7-day larval fish growth and survival test used in the United States, for example. Addressing these needs by via workshops, research, and additional data reviews were identified for future action by scientists and regulators.